BILATERAL TRADE FLOWS AMONG G7 MEMBER COUNTRIES AND INDONESIA: GRAVITY MODEL APPROACH - Abshar Ramadhanny Subhan; Budi Santosa; Soeharjoto Soeharjoto (Media Ekonomi, 2021)
This study aims to analyze the determining factors that determine the bilateral trade flow among G7 member countries and Indonesia. This study uses the gravity model of trade as concepted by Timbergen (1962). Panel Regression Analysis with Fixed Effect Method is conducted in order to acknowledge the relationship between Gross Domestic Product (GDP), PerCapita Gross Domestic Product (PCGDP), Exchange Rate (ER), Population (POP), and Distance (DIST) on G7’s Bilateral Trade Flows (BTF) while the data used are both time series (2007-2016) and cross sectional. This study used secondary data obtained from the World Bank, CEPII, UN Comtrade, OECD and ITC Trade Map. The results of this study simultaneously and partially proved that the independent variables as mentioned above definetely have impact on G7’s Bilateral Trade Flows, thus specifically the results show PerCapita Gross Domestic Product (PCGDP), Population (POP), and Distance (DIST) had significant influence on G7’s Bilateral Trade Flows.